Effect of sodium content on the structure and mechanical properties of silicon bronze (Cu-3wt%Si alloys) - Chikezie Walter Onyia; EE Nnuka; KC Nnakwo; SE Ede (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
In the present study, the effect of sodium content on the structure and mechanical properties of Cu-3wt%Si alloys were investigated. The experimental alloys were produced with various sodium concentrations of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2 and 3% by weight using permanent mould casting technique. Tensile and hardness tests were carried out on the cast samples. Microstructures of the specimens were also analysed using optical microscopy. The results indicated that the addition of sodium to Cu-3wt%Si alloy refined and modified the structure of the alloy resulting in improvement in the ultimate tensile strength and hardness of the experimental alloy by 453.85% and 58.82% respectively at 1.5wt%Na content and percentage elongation by 168.81% at 0.1wt%Na content. The addition of sodium also led to the formation of the Na1.44Si136 intermetallic phase which further contributed to the increase in strength and hardness of the alloy.